Aesthetic Exploration In Prosthesis Design For Lower Limb - Ting, Cheng Wean (Universiti Malaysia Sarawak(UNIMAS), 2018)
In Malaysia, the number of limb amputation is increasing yearly and the main reason is diabetes. Amputees need to depend on prosthesis limb so that they can walk and stand again. Most of the amputees may faces volume changes every single hour of every single day in their residual limb and which may lead their residual limb cant fit the socket of the prosthesis properly. Hence, most of the amputees face the difficulties of wearing the prosthesis leg all the time. Amputees may need to replace a new socket so they can put on the prosthesis leg again and the price is high. Amputees have low confident level after they were using their prosthesis leg, they found they were still abnormal compared to others. The objectives of this research are to identify the type of prosthesis and the suspension mechanism, to analysis the needs of amputees in term of comfort level and the cosmetic appearance of prosthesis, to propose a practical and aesthetic design if prosthesis and to validate the perception of aesthetic in the design of prosthesis. Both qualitative and quantitative approaches were used to conduct this research. In this study, researcher will propose a design on prosthesis leg that have an adjustable socket and high in aesthetic value prosthesis leg so that amputee can wear the prosthesis leg when they are facing volume changes in their residual limb and increase their confident level.